Performance Preparation, Anxiety, and the Teacher. Experiences of Adolescent Pianists - Ryan, Charlene; Boucher, Hélène; Ryan, Gina (Revue musicale OICRM, 2021)
The purpose of this study was to examine the experiences of adolescent pianists in their private lessons and solo performances in regard to concert preparation and music performance anxiety (mpa). A particular focus was placed on the student-teacher relationship and the potential role of teachers in students’ preparation, experience, and anxiety in performance situations. 62 piano students completed questionnaires pertaining to their private lessons, teacher, and performance experiences, as well as two inventories—one pertaining to self-esteem and the other on music performance anxiety. Results indicate that self-esteem and practice are significant predictors of mpa, with self-esteem having the most notable effect. Almost half of the participants reported feeling nervous in their lessons at least some of the time. Most students noted that their teachers encourage them to perform; however, only half reported that their teachers address performance preparation issues. Less than half were reported to discuss memorization strategies or management of mpa with students, or to hold practice-performance classes. Implications for music educators and future research directions are discussed.